Sheikh Muhammad Al-Saeed Al-Zemmoushi's reformist work and the national struggle in the Algerian national movement: a biography (1904-1960) - ben abdel moumene, Ibrahim (The Algerian Historical Journal, 2026)
This article monitors the biography of Sheikh Mohammed Al-Saeed Al-Zamoushi as a reformer throughout the Algerian national movement. He played a significant role in the reform and political struggle against the French occupation policies in Algeria, and we can notice his profound influence by simply reading his biography in this article, which focuses mostly on its events that took place in the Western Algerian region during three decades. Sheikh Al-Zamoushi, a native of the far-Eastern Algerian city of Ain Al Bayda, was active in Mascara, Oran, Tlemcen, and several other cities. As one of the members of the Association of Algerian Muslim Ulama (scholars).